Analysis of Learning Methods of Grade IV and V Outstanding Students at SD N Tanggan 2 - Hendra Tri Wahyono; Nur Amalia (Eduvest - Journal of Universal Studies, 2024)
Learning is an activity that a person does for behavior change that manifests as an experience that can be in the form of increasing knowledge, changing behavior, and changing attitudes. This study aims 1) to describe the grade IV and V outstanding student’s learning method at SD N Tanggan 2, and 2) to describe what factors affect the learning achievement of grades IV and V outstanding students at SD N Tanggan 2. This research method uses qualitative methods carried out at SD Tanggan 2. The object of this study is the Learning method of Outstanding Students and the subjects in this study are class teachers and student of grade IV & V. The data analysis technique in this study refers to the Miless and Huberman model. The results showed 1) Outstanding students of grades IV and V of SD N Tanggan 2 have learning methods such as asking questions when meeting difficult questions, asking questions when they do not understand the material, paying attention to the teacher's explanation, repeating lessons, and double-checking assignments carefully. 2) The learning achievement of SD N Tanggan 2 students is influenced by two factors, namely internal factors and external factors.